Tutorials in Endovascular Neurosurgery and Interventional Neuroradiology - Byrne, James Vincent (Springer Berlin Heidelberg, 2012)
This book aims to provide the trainee and practicing minimally invasive neurological therapist with a comprehensive understanding of the background science and theory that forms the foundation of their work. The contents are based on the tutorial teaching techniques used at the University of Oxford and are authored by the MSc Course Director. The tutorial is a learning episode focussed on a particular topic and intended to guide the student/reader through the background literature, to highlight the research on which standard practices are based and to provide the insights of an experienced practitioner. Each chapter of the book covers a different topic to build a complete review of the subspecialty, with in-depth discussion of all currently used techniques. The literature is reviewed and presented in context to illustrate its importance to the practice of this rapidly expanding field of medical treatment
Keywords: Neuroradiology; Neurology; Neurosurgery; Minimally Invasive Surgery; Neurology; Minimally invasive surgery; Interventionsradiologie; Gefäßchirurgie; Neurochirurgie